PEDIATRIC CLINICAL TRIALS: FROM ENCOURAGEMENT TO REGULATORY REQUIREMENTS - I.V. Smolenov (Педиатрическая фармакология, 2010)
Prescription of a drug for children is often accompanied with failure to follow the indications, methods of administration, dosages recommended (as a rule, for adults) by product directions. The article illustrates factors that prevent the conduct of clinical trials involving children on a larger scale. As a result, for most drugs there are no data on their efficacy, safety, required doses, optimal ways of administration, etc. Currently to improve this situation, new regulations, rules, requirements are being drafted that on the one hand, encourage, and, on the other hand, require pharmaceutical companies to conduct pediatric trials. Key words: drugs, clinical trials, children. (Pediatric Pharmacology. – 2010; 7(4):7-11)